Dampak Pertumbuhan Ekonomi, Jumlah Penduduk Dan Belanja Modal Terhadap Pendapatan Asli Daerah - Diana Purnama Lestari; Swarmilah Hariani (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
This study aims to determine the impact of economic growth, population, and capital expenditure on the original income of the district/city in Bengkulu Province. The population of this study is all regencies/cities in Bengkulu Province, amounting to 9 districts and 1 city. The sample consists of the entire population, using local government financial reports, regional financial statistical reports, and regional statistical reports for the period 2014 - 2018. The analytical method used in this study is the multiple linear regression analysis. The results of the study concluded that economic growth had a positive and significant impact on regional own-source revenue, the population had a positive and significant impact on regional own-source revenue, while capital expenditure had a positive and not significant effect on regional own-source revenuen.